2022
DOI: 10.3389/fpsyg.2022.963666
|View full text |Cite
|
Sign up to set email alerts
|

A novel task to evaluate irony comprehension and its essential elements in Spanish speakers

Abstract: An ironic statement transmits the opposite meaning to its literal counterpart and is one of the most complex communicative acts. Thus, it has been proposed to be a good indicator of social communication ability. Prosody and facial expression are two crucial paralinguistic cues that can facilitate the understanding of ironic statements. The primary aim of this study was to create and evaluate a task of irony identification that could be used in neuroimaging studies. We independently evaluated three cues, contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…This result agrees with our previous behavioral study (26) and with the proposal that irony is one of the most difficult communication forms (5). With regard to the neural regions involved, we found that the precuneus, which has been associated with ToM, presented consistent activation during the detection of the ironic statements.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result agrees with our previous behavioral study (26) and with the proposal that irony is one of the most difficult communication forms (5). With regard to the neural regions involved, we found that the precuneus, which has been associated with ToM, presented consistent activation during the detection of the ironic statements.…”
Section: Discussionsupporting
confidence: 93%
“…The contextual discrepancy task we employed showed that ironic statements were difficult to detect, having the lowest accuracy and highest classification latency. This result agrees with our previous behavioral study (Valles-Capetillo et al, 2022) and with the proposal that irony is one of the most difficult communication forms (Wilson & Sperber, 1981). Regarding the neural regions involved, we found that the precuneus, which has been associated with ToM, presented consistent activation during the detection of the ironic statements.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations